An experimental and theoretical study into NaSbS2 as an emerging solar absorber. Issue 7 (29th January 2019) - Leung, W. W. Winnie; Savory, Christopher N.; Palgrave, Robert G.; Scanlon, David O.
Abstract : NaSbS2 has recently been proposed as an emerging solar cell material, however in this study we demonstrate that it may be limited by a forbidden band gap, and instead possesses a more suitable electronic structure for thermoelectrics. Abstract : As photovoltaics have grown to become one of the dominant renewable energy generating technologies, attention has fallen upon thin-film materials as a route to lightweight, flexible and portable solar cells. NaSbS2 has recently been proposed as a non-toxic, earth abundant solar absorber for thin-film cells. In this study, we use a combined theoretical and experimental approach to characterize and assess the electronic and optical properties of NaSbS2 as an emerging solar absorber. Our results, utilising two theoretical efficiency metrics, demonstrate that NaSbS2 may be limited for use in single-junction cells by a forbidden band gap and slow absorption onset. Other features of its electronic structure, however, indicate that the material may still be promising in thermoelectric applications.